Risk Factors Associated With Perioperative Complications and Prolonged Length of Stay After Laparoscopic Adrenalectomy - Chen, Yufei; Scholten, Anouk; Chomsky-Higgins, Kathryn; Nwaogu, Iheoma; Gosnell, Jessica E; Seib, Carolyn; Shen, Wen T; Suh, Insoo; Duh, Quan-Yang (JAMA surgery, 2018)
Laparoscopic adrenalectomy is the gold standard for most adrenal disorders and its frequency in the United States is increasing. While national and administrative databases can adjust for patient factors, comorbidities, and institutional variations, granular disease-specific data that may significantly influence the incidence of perioperative complications and length of stay (LOS) are lacking. To investigate factors associated with perioperative complications and LOS after laparoscopic adrenalectomy. This cohort study was carried out at a single academic medical center, with all patients who underwent laparoscopic adrenalectomy between 1993 and 2017 by the endocrine surgery department. Multivariable linear and logistic regression were used to obtain adjusted odds ratios (ORs). The primary outcome was perioperative complications with a Dindo-Clavien grade of 2 or more. The secondary outcome was prolonged length of stay, defined as a stay longer than the 75th percentile of the overall cohort. We identified 640 patients who underwent 653 laparoscopic adrenalectomies, of whom 370 (56.7%) were female. The median age was 51 (range, 5-88) years. A total of 76 complications with a Dindo-Clavien grade of 2 or more occurred in 55 patients (8.4%), with postoperative mortality in 2 patients (0.3%). The median hospital length of stay was 1 day (range, 0-32 days). Factors independently associated with increased complications were American Society of Anesthesiologists class 3 or 4 (OR, 2.78 [95% CI, 1.39-5.55]; P < .01), diabetes (OR, 2.39 [95% CI, 1.14-5.01]; P = .02), conversion to hand-assisted or open surgery (OR, 5.32 [95% CI, 1.84-15.41]; P < .01), a diagnosis of pheochromocytoma (OR, 4.31 [95% CI, 1.43-13.05]; P = .01), and a tumor size of 6 cm or greater (OR, 2.47 [95% CI, 1.05-5.78]; P = .04). Prolonged length of stay was associated with age 65 years or older (OR, 2.44 [95% CI, 1.31-4.57]; P = .01), an American Society of Anesthesiologists class 3 or 4 (OR, 3.48 [95% CI, 1.88-6.41]; P < .01), any procedural conversion (OR, 63.28 [95% CI, 12.53-319.59]; P < .01), and a tumor size of 4 cm or larger (4-6 cm: OR, 2.38 [95% CI, 1.21-4.67]; P = .01; ≥6 cm: OR, 2.46 [95% CI, 1.12-5.40]; P = .03). Laparoscopic adrenalectomy remains safe for most adrenal disorders. Patient comorbidities, adrenal pathology, and tumor size are associated with the risk of complications and length of stay and should all be considered in selecting and preparing patients for surgery.